If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(3x + -2) + -6 = 3(2x + -4) Reorder the terms: 6(-2 + 3x) + -6 = 3(2x + -4) (-2 * 6 + 3x * 6) + -6 = 3(2x + -4) (-12 + 18x) + -6 = 3(2x + -4) Reorder the terms: -12 + -6 + 18x = 3(2x + -4) Combine like terms: -12 + -6 = -18 -18 + 18x = 3(2x + -4) Reorder the terms: -18 + 18x = 3(-4 + 2x) -18 + 18x = (-4 * 3 + 2x * 3) -18 + 18x = (-12 + 6x) Solving -18 + 18x = -12 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -18 + 18x + -6x = -12 + 6x + -6x Combine like terms: 18x + -6x = 12x -18 + 12x = -12 + 6x + -6x Combine like terms: 6x + -6x = 0 -18 + 12x = -12 + 0 -18 + 12x = -12 Add '18' to each side of the equation. -18 + 18 + 12x = -12 + 18 Combine like terms: -18 + 18 = 0 0 + 12x = -12 + 18 12x = -12 + 18 Combine like terms: -12 + 18 = 6 12x = 6 Divide each side by '12'. x = 0.5 Simplifying x = 0.5
| 2b-3-11b-9= | | (200000-X)*0.2=80000-X | | x/35=60/100 | | x/250=108/100 | | a^2x^2+abx-2b=0 | | 7(a+8)=63 | | 76+x=82+y | | 11x/12+5/12=x-2 | | 76+x=82+x | | X^2-6x-9=7 | | (a+b)(3ab+b^2)=0 | | 3m+5=12-m | | 8-q=10 | | 5(3h-2)=4-12r | | x/10=9 | | 6x-4=4x+12 | | 4=x/6 | | 10x^2+2x-4=0 | | 2x^4+5x^2-207=0 | | 10x+2x-4=0 | | 4e^7x=8 | | 0=-16t^2+328 | | 4x^2-24x+5=0 | | x^4-3x^2=4 | | 3x^3+x^2-21x+14=0 | | 2v=0 | | 8=x/7 | | 3+10x-2=4x-12+16 | | 4-2x=5-3(x-1) | | 4-2x=5-3 | | 21x^2-25x=4 | | (x+y+1)dx+(2x+2y-1)dy=0 |